Health care disparities for incarcerated adults after a suicide attempt. Issue 5 (29th June 2021) - Fedock, Gina; Garthe, Rachel; Higgins, George E.; Lewis, Cashell; Blank Wilson, Amy
Abstract: Objective: Incarcerated adults have high rates of fatal and nonfatal suicidal behaviors. Suicide prevention recommendations stress the need for the provision of health care for incarcerated adults after suicide attempts, yet prison policies and practices often focus instead on punitive responses to suicidal behaviors. Existing research is limited regarding factors that predict the provision of health care to incarcerated adults post‐suicide attempt. The current study examined individual, incident, and institutional factors as predictors of health care to incarcerated adults post‐suicide attempt. Method: We used data from critical incidents reports for suicide attempts ( N = 495) to conduct mixed‐effects logistical regression models. Results: Staff responded to suicide attempts by placing incarcerated adults under direct observation (with no care) or in segregation at odds two and three times higher than of providing health care, particularly in prisons for men. Race was a significant factor; incidents involving Black men were less likely than incidents involving white men to include staff requesting health care, and incidents involving Black women were less likely than incidents involving white women to include requesting and providing health care. Conclusions: This study's findings highlight factors predicting health care responses to suicide attempts and the need to address and prevent health care disparities in prisons.